1981
DOI: 10.1111/j.1528-1157.1981.tb06152.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonazepam (Rivotril®) and Carbamazepine (Tegretol®) in Psychomotor Epilepsy: A Randomized Multicenter Trial

Abstract: The antiepileptic properties of carbamazepine (Tegretol) and clonazepam (Rivotril) were compared in a double-blind randomized study comprising 36 patients with newly diagnosed, untreated psychomotor epilepsy (partial seizures with complex symptomatology). No significant differences were found between the two drugs during the 6 months of treatment. Measurements of concentrations in plasma confirmed that the patients exceeded the accepted lower limit for therapeutic range of the drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Many reports are double-blind studies comparing the antiepileptic effect of carbamazepine with that of phenytoin, clonazepam or valproate (Callaghan et al 1985;Mikkelsen et al 1981;Ramsay et al 1983;Simonsen et al 1976;Troupin et al 1977). These studies have not been designed with the primary aim of investigating the plasma concentration-effect relationship.…”
Section: Total Plasma Concentration and Clinical Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Many reports are double-blind studies comparing the antiepileptic effect of carbamazepine with that of phenytoin, clonazepam or valproate (Callaghan et al 1985;Mikkelsen et al 1981;Ramsay et al 1983;Simonsen et al 1976;Troupin et al 1977). These studies have not been designed with the primary aim of investigating the plasma concentration-effect relationship.…”
Section: Total Plasma Concentration and Clinical Effectsmentioning
confidence: 94%
“…The study of Shorvon et al (1980), like others (Callaghan et al 1985;Mikkelsen et al 1981;Ramsay et al 1983;Sillanpaa et al 1979;Strandjord & Johannessen 1980), comprised newly diagnosed, previously untreated patients. Seizure control at lower plasma concentrations appears to be more common in this patient category.…”
Section: Total Plasma Concentration and Clinical Effectsmentioning
confidence: 95%
“…In a study of 36 children and adults with newly diagnosed complex partial seizures, Mikkelsen et al (1981) reported no difference between carbamazepine and clonazepam in the number of patients who became completely seizure free in 6 months (49% versus 46%). Patients in this study were included regardless of age and number of seizures.…”
Section: Complete Seizure Controlmentioning
confidence: 98%
“…In the assessment of the efficacy of antiepileptic drugs, five criteria may be used in this determination: Rodin et al, 1974 Carbarnazepine vs. phenytoin Rajotte et al, 1967Sirnonsen et al, 1976Troupin et al, 1977Kosteljanetz et al, 1979Ramsay et al, 1983Majerrison et al, 1968Rodin et al, 1976Mikkelsen et al, 1981 phenobarbital Cereghino et al, 1974 Carbarnazepine vs. phenytoin vs. phenobarbital vs. primidone Mattson et al, 1985 Carbarnazepine vs. phenytoin and/or phenobarbital and/or primidone Bird et al, 1966placebo Gruber et al, 1956 primidone vs. placebo White et al, 1966Phenytoin vs. pheneturide Gibberd et al, 1982Phenobarbital vs. clorazepate Wilensky et al, 1981Valproic acid vs. placebo Richens and Ahmad, 1975Gram et al, 1977Valproic acid vs. valproic acid Gram et al, 1979 Carbamazepine vs. phenobarbital -5. the duration of time patients remain on a drug (i.e., how long the drug remains sufficiently effective with sufficiently few side effects for the patient to continue using that drug rather than switching to another). -This review considers the results from the 20 controlled trials, discussed here in the context of these criteria for the evaluation of the efficacy of antiepileptic drugs.…”
Section: Efficacy Of Antiepileptic Drugsmentioning
confidence: 99%
“…Oral diazepam became obsolete. Clonazepam began to be used as an adjunct in drug-resistant patients and as a first-line agent in Scandinavian countries (16). Attention also was called to the superiority of clobazam by Gastaut and Low (17).…”
Section: The Drug Choicementioning
confidence: 99%